Active packaging for table grapes: Evaluation of antimicrobial performances of packaging for shelf life of the grapes under thermal stress. (September 2020) - Gorrasi, Giuliana; Bugatti, Valeria; Vertuccio, Luigi; Vittoria, Vittoria; Pace, Bernardo; Cefola, Maria; Quintieri, Laura; Bernardo, Paola; Clarizia, Gabriele
Highlights: Active coating were prepared using LDH and salicylate. Active packaging were used for table grapes. Reduction in total mesophilic aerobic count, mould and yeast were observed. Theoretical prediction of shelf life of the packed grapes was presented. Abstract: The paper reports the formulation of an active packaging based on PET coated with a Layered Double Hydroxide (LDH) hosting 2-acetoxybenzoic anion (salicylate) as antimicrobial molecule. The release of the molecule anchored to the LDH, compared to the molecule free dispersed into the coating, appeared much slower. Permeability of carbon dioxide and oxygen through the packaging at different temperatures was evaluated, as well as the capability of the active material to inhibit Pseudomonas, Listeria and Lactobacillus . Table grape was stored in thermal stress conditions ( i.e . 10 °C) into the active packaging and the total mesophilic aerobic count and yeasts and moulds population was evaluated up to 14 days of storage. The experimental results were used for a theoretical prediction of shelf life of the packed grapes and compared with the same fruit packed into untreated material. Global and specific migration of salicylic acid from the active packaging demonstrated, in compliance with the migration limits of the EU regulation, the suitability of the considered material for food contact.